PENGARUH URUTAN BUKTI, GAYA KOGNITIF, DAN PERSONALITAS TERHADAP PROSES REVISI KEYAKINAN - Damai Nasution; Supriyadi , (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
Researches that tried to examines effect of evidence order and individual psychological dimensions, consist of cognitive style and personality, to auditors’ judgment never been examined in auditing, especially, in belief-revision context. Present research is first. Present research focused on examination the influence of evidence order, cognitive style, and personality to auditors’ judgment. Judgment in this research is define to how auditor revised his believe based on evidence that evaluated step-by-step. Experiment method use in this research. Using a case study out of to 88 auditor, this research found that: (i) auditors’ judgment were affected by order in which audit evidences was evaluated;(ii) when auditor evaluated evidences in reverse order (- - + + vs. + + - -), recency effect occur. This finding show that auditor will weighted disconfirmation evidence more important than confirmation evidence; (iii) interaction exist between evidence order, cognitive style, and personality to affect auditors’ judgment.